Detection of monoclonality in intestinal lymphoma with polymerase chain reaction for antigen receptor gene rearrangement analysis to differentiate from enteritis in dogs. (18th May 2015) - Ohmura, S.; Leipig, M.; Schöpper, I.; Hergt, F.; Weber, K.; Rütgen, B. C.; Tsujimoto, H.; Hermanns, W.; Hirschberger, J.
Abstract: The diagnosis of canine intestinal lymphoma by morphological examination is challenging, especially when endoscopic tissue specimens are used. The utility of detection of antigen receptor gene rearrangement by polymerase chain reaction (PARR) in canine lymphoma has been well established, but its usefulness to distinguish enteritis and intestinal lymphoma remains unclear. In this retrospective study we assessed clonality of 29 primary canine intestinal lymphoma, 14 enteritis and 15 healthy control cases by PARR analysis, using formalin‐fixed, paraffin‐embedded full‐thickness tissue specimens. We could detect monoclonal rearrangements in 22 of 29 canine intestinal lymphomas [76%; 95% confidence interval (CI) 56–90%] and polyclonal rearrangements in all of the enteritis and healthy control cases (100%; CI 88–100%). We revealed a predominance of T‐cell phenotype compared to B‐cell phenotype (85%; CI 65–96% and 15%; CI 4–35%, respectively). We showed that PARR analysis contributes to differentiation of canine intestinal lymphoma from enteritis and to phenotyping of lymphomas.